Lack of fitness costs in dsRNA-resistant Leptinotarsa decemlineata ([Coleoptera]: [Chrysomelidae]) - Pinto, M. M. D. [UNESP]; Santos, R. Ferreira dos; Bortoli, S. A. de [UNESP]; Moar, W.; Jurat-Fuentes, J. L. (Oxford Univ Press Inc, 2023)
The Colorado potato beetle, Leptinotarsa decemlineata (Say) ([Coleoptera]: [Chrysomelidae]), is the most important defoliator of solanaceous plants worldwide. This insect displays a notorious ability in adapting to biological and synthetic insecticides, although in some cases this adaptation carries relevant fitness costs. Insecticidal gene silencing by RNA interference is a novel mode of action pesticide against L. decemlineata that is activated by ingestion of a double stranded RNA (dsRNA) targeting a vital L. decemlineata gene. We previously reported laboratory selection of a > 11,000-fold resistant strain of L. decemlineata to a dsRNA delivered topically to potato leaves. In this work, we tested the existence of fitness costs in this dsRNA-resistant colony by comparing biological parameters to the parental strain and an additional susceptible reference strain. Biological parameters included length of egg incubation period, number of eggs per clutch, egg viability, larval viability, length of larval and pupal periods, adult emergence, number of eggs laid per day, sex ratio, and adult longevity. Comparisons between the 3 beetle strains detected no fitness costs associated with resistance to dsRNA. This information is important to guide effective insect resistance management plans for dsRNA insecticides against L. decemlineata applied topically to potato leaves.
Keywords: double-stranded RNA; RNA interference; resistance; fitness cost